Dominasi Struktur Kalimat dan Pilihan Kata dalam Esai Mahasiswa Asing pada Tes Kemampuan Berbahasa Indonesia - Kaniah Kaniah; Dian Palupi (Badan Pengembangan dan Pembinaan Bahasa, 2020)
This study aims to describe the sentence structure and choice of words in foreign students' essays on the Indonesian language proficiency test. This research is qualitative with descriptive method. The data source of this research is the essay of foreign students who took the Indonesian language proficiency test. The research data are Indonesian words and sentences contained in the student essays. The data analysis technique was carried out through the steps, namely (a) data identification, (b) data classification, and (c) data interpretation. The results showed that foreign students were able to write simple sentences in Indonesian, but had difficulty understanding the affix process.